Relationship between childhood body mass index and young adult asthma - Porter, Minto (2012)
BACKGROUND: The relationship between obesity and asthma is an area of debate. OBJECTIVE: To investigate the association of elevated body mass index (BMI) at a young age and young adult asthma. METHODS: BMI, questionnaires, and serologic tests results were analyzed in participants of a predominantly white, middle-class, population-based birth cohort from Detroit, Michigan at 6 to 8 and 18 years of age. Asthma diagnosis was based on medical record data. Allergen specific IgE was analyzed using UniCAP, with atopy defined as 1 or more allergen specific IgE levels of 0.35 kU/L or higher. Overweight was defined as a BMI in 85th percentile or higher. RESULTS: A total of 10.6% of overweight males at 6 to 8 years of age had current asthma at 18 to 20 years of age compared with 3.2% of males who were normal or underweight (relative risk [RR], 3.3; 95% confidence interval [CI], 1.0–11.0; P=.048). A total of 19.6% of females who were overweight at 6 to 8 years of age had asthma compared with 10.3% of females who were normal or underweight (RR, 1.9; 95% CI, 0.9–3.9; P=.09). After adjustment for atopy at 6 to 8 years of age, overweight males had an adjusted RR of 4.7 (95% CI, 1.4–16.2; P=.01), and overweight females had an adjusted RR of 1.7 (95% CI, 0.8–3.3; P=.15). Change in BMI between 6 to 8 years of age and 18 to 20 years of age was also examined. Patients with persistently elevated BMI exhibited increased risk of asthma as young adults (RR, 2.4; 95% CI, 1.2–4.7) but not with an increasing BMI (RR, 0.8; 95% CI, 0.3–2.2) or a decreasing BMI (RR, 0.8; 95% CI, 0.3–2.2). CONCLUSION: Overweight males 6 to 8 years of age have increased risk of asthma as young adults. Being overweight remains a predictor of asthma after adjustment for early atopy. A similar but not statistically significant trend was also seen among overweight females. Overweight body habitus throughout childhood is a risk factor for young adult asthma.